Biochemical assessment of oat genotypes revealed variability in grain quality with nutrition and crop improvement implications. (30th May 2022) - Poonia, Atman; Phogat, D.S.; Versha; Nagar, Sushil; Sharma, Paras; Kumar, Vinod
Highlights: A wide range of protein content (127.0 to 160.50 mg/g) was observed among 112 oat genotypes tested. A significant positive correlation was found between Fe and Mn (r = 0.29). The oat cultivars HFO-910, SUBZAR, HFO-921, HFO-50, OL-9, HFO-638, and JO-1 had 1.60-fold higher Fe content than the average value. The oat cultivar HFO-587 exhibited the lowest phytic acid content (1.0 mg/g). Beta-glucan content ranged between 13.80 and 53.50 mg/g across the evaluated samples. Abstract: Oat is a potent source of nutrients and bioactive compounds offering potential health benefits and role in combating micronutrient malnutrition problems. To exploit nutritional and quality traits of oats, a biochemical assessment of 112 oat genotypes was conducted. The high range of variability for total phenol (1.7–31.3 mg/g), β-glucan (1.0–8.0 mg/g), calcium (1.91–4.34 mg/g), zinc (3.80–6.50 mg/100 g), iron (0.66–4.89 mg/100 g) and manganese (2.88–8.0 mg/100 g) was revealed among genotypes. A higher amount of iron and zinc was found in genotypes OS-6, HFO-638, HFO-915 & HFO-918, whereas, elevated levels of manganese and zinc were recorded in genotypes OS-403 & OL-1804. The results revealed groups of low phytic acid oat genotypes containing high crude protein (HFO-52, HFO-270, HFO-330), β-glucan (HFO-62, HFO-588, HFO-926). A significant positive correlation was obtained between copper with iron, manganese, and calcium content. These findings could be useful for developing value-added oat food products and novel oat varieties.